Effect Addition of Potato Flour to Physical Characteristic of Beef Meatballs - Harapin Hafid (Jurnal Peternakan Integratif, 2026)
Meat is a food ingredient that is currently being modified into a food that is popular with consumer. This study aims to evaluate the effect of adding potato starch on the physical and organoleptic quality of beef meatballs. A completely randomized design (CRD) with 5 treatments and 5 replications was used in the study. The treatments were 5% potato starch (P1), 10% potato starch (P2), 15% potato starch (P3), 20% potato starch (P4) and 25% potato starch (P5). The parameters observed were physical quality including the degree of acidity (pH), cooking loss, water holding capacity, and rendement. The results of the study showed that the physical quality of beef meatballs with the addition of potato starch had a significant effect on water holding capacity, but there was no significant effect (P>0.05) on the degree of acidity (pH), cooking loss and rendement